1987
DOI: 10.1007/bf00015030
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal DNA methylation in a flax genotroph and a crown gall tumour

Abstract: The methylation patterns of two flax lines are described. One, a genotroph S1, has 800 rNA genes per haploid cell while FT37/1, a crown gall tumour incited on S1, has only 300. Using the enzymes EcoRII, BstNI and ApyI to assess CXG methylation and HpaII and MspI for CG, we show that the methylation patterns of the rDNAs of both lines are identical. Both lines contain 3 fractions; the first contains repeats that are methylated at all sites examined and the second has some unmethylated sites. The third fraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The rDNA was highly resistant to Hpa II cleavage but was cleaved extensively by Msp I. Similar fractionation of rDNA by methylationsensitive restriction enzymes has been reported for several plant species [8,10,13,15,25,36,40,41 ]. Using the published sequences from the IGS of BMS [23] (or A619 [39]), the 18S gene of maize line W22 [21] and the 26S gene office [37] to provide a sequence of an entire repeat unit indicates that, on average, there would be approximately 70 CCGG sites per repeat unit present in maize and teosinte.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The rDNA was highly resistant to Hpa II cleavage but was cleaved extensively by Msp I. Similar fractionation of rDNA by methylationsensitive restriction enzymes has been reported for several plant species [8,10,13,15,25,36,40,41 ]. Using the published sequences from the IGS of BMS [23] (or A619 [39]), the 18S gene of maize line W22 [21] and the 26S gene office [37] to provide a sequence of an entire repeat unit indicates that, on average, there would be approximately 70 CCGG sites per repeat unit present in maize and teosinte.…”
Section: Discussionmentioning
confidence: 56%
“…This conclusion is further supported by the evolutionary conservation of this region of undermethylation. Studies of numerous other plant rDNAs have identified the primary site of undermethylation at approximately 0.7-1.0kb upstream of the start of the 18S coding region [8,13,14,15,40,41]. Conservation of this general location of undermethylation also has been observed in Xenopus rDNA [6].…”
Section: Discussionmentioning
confidence: 86%
“…However, other known mechanisms might play a role in our study as well, such as (a) a differential transposition of somatically active transposable elements, which have been described in, so far, both invertebrates and vertebrates [43,44] or (b) the presence of heritable changes involving DNA within a single generation that have been observed in the annual flax [45]. We cannot exclude from our consideration the possibility of environmentally induced changes of genome size, as these changes have been observed during cell culturing [46][47][48]. Also, observed genome size changes may have been associated (not necessarily directly selected for) with changes in cell volume and/or in karyoplasmatic ratio.…”
Section: Selection For Genome Size In Cyclamen?mentioning
confidence: 95%
“…There are several studies indicating differential methylation of rDNA repeats and some evidence that hypomethylation Abbreviations: azaC=azacytidine; bp=basepairs; mC=methyl-ated cytosine; CpG=deoxycytidine-phosphate-deoxyguanosine; X (in CpXpG)= any deoxyribonucleoside of a specific region in the intergenic spacer could regulate the expression of the rDNA genes (Ellis et al 1983;von Kalm et al 1986;Blundy et al 1987;Jupe and Zimmer 1990). There may also be differences in the methylation status of the DNA of developed plant organs and dedifferentiated callus (Reddy et al 1988;LoSchiavo et al 1989;Brown 1989;Brown et al 1989;Vergara et al 1990).…”
Section: Introductionmentioning
confidence: 98%